2021
DOI: 10.1111/liv.14786
|View full text |Cite
|
Sign up to set email alerts
|

Switching from entecavir to tenofovir alafenamide for chronic hepatitis B patients with low‐level viraemia

Abstract: Background and Aims: About 20% of patients receiving nucleos(t)ide analogues treatment experienced low-level viraemia (LLV), which is associated with progression of liver fibrosis and high risk of hepatocellular carcinoma. We aimed to evaluate the effectiveness and safety of switching from entecavir (ETV) to tenofovir alafenamide fumarate (TAF) in ETV-treated patients with LLV.Methods: In this prospective study, ETV-treated patients with LLV, presented to our hospital from December 2018 to October 2019, were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 32 publications
5
46
0
Order By: Relevance
“…Moreover, Hagiwara et al reported similar degrees of reduction of the serum HBsAg level between patients in whom the nucleos(t)de analog was switched from ETV to TAF and those who had received ETV monotherapy [18,19]. Similar results were also reported by Itokawa et al [20], Li ZB et al [21], and Tamaki N, et al [22]. There were limitations of these studies, e.g., small study sample sizes [18,19,21,22], short TAF administration period (24 weeks) [21], and different sites of measurement of the serum HBsAg levels [17,20].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, Hagiwara et al reported similar degrees of reduction of the serum HBsAg level between patients in whom the nucleos(t)de analog was switched from ETV to TAF and those who had received ETV monotherapy [18,19]. Similar results were also reported by Itokawa et al [20], Li ZB et al [21], and Tamaki N, et al [22]. There were limitations of these studies, e.g., small study sample sizes [18,19,21,22], short TAF administration period (24 weeks) [21], and different sites of measurement of the serum HBsAg levels [17,20].…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, the McNemar test revealed that the antiviral efficacy of TAF was superior to that of ETV when increase and decrease of the serum HBsAg level by 0.08 Log IU/mL/48 weeks or more were defined as "increase" and "decrease," respectively (P = 0.022) [11]. Controversy exists, however, as to whether TAF exerts superior efficacy to ETV in reducing the serum HBsAg level [16][17][18][19][20][21]. Kumada T, et al reported results similar to ours [11] in patients in whom the nucleos(t)ide analog used for treatment was switched from ETV to TAF [16]; on the other hand, Ogawa E, et al [17] did not find any superiority of TAF over ETV, in terms of the efficacy of the drugs in reducing the serum HBsAg levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous global phase III clinical studies 108/110 on TAF[ 18 , 19 ] showed that compared with TDF, CHB patients treated with TAF could achieve a higher proportion of ALT normalization at both the 48 th and 96 th weeks. Moreover, an increasing number of real-world studies[ 20 - 22 ] demonstrated that about 30% of CHB patients receiving long-term ETV therapy failed to achieve complete virological response (the lower limit of detection of HBV DNA was 20 IU/mL), while most patients could achieve complete virological response after switching to TAF therapy. All these studies suggest that TAF has more prominent advantages in antiviral ability and/or ALT normalization.…”
Section: Discussionmentioning
confidence: 99%
“…For ETV-treated patients with LLV, switching to TAF is safe enough and superior compared with continuing ETV monotherapy regarding both virological and biochemical benefits. [ 50 ] All the above studies have suggested that in the context of the occurrence of LLV, switching to another drug is more conducive to attaining a CVR.…”
Section: Management Of Llvmentioning
confidence: 99%